2022
DOI: 10.3390/ijerph192215280
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Eating Habits of Polish Young Adults Aged 20–26

Abstract: The aim of the study was to examine the nutritional behaviour of young adults depending on gender. A survey was conducted among 467 young adults using the “Questionnaire for the study of nutritional behaviour and opinions on food and nutrition”. Questions concerned the frequency of consumption of selected groups of food products. The questionnaire was supplemented by questions regarding the number of portions of fruits and vegetables consumed, putting sugar in drinks, putting salt in dishes and the number of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This is very much in line with the results from the German EsKiMo study according to which boys also consumed 50% more than girls—the median weekly intake among boys was 42 g, while among girls 28 g [ 53 ]. The higher fish intake among males, even though many studies indicate that women often have healthier food choices than men [ 54 , 55 , 56 ], might be due to the fact that men simply consume bigger food portions [ 57 , 58 ] and more energy [ 59 ], but also more animal protein [ 60 ] than women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very much in line with the results from the German EsKiMo study according to which boys also consumed 50% more than girls—the median weekly intake among boys was 42 g, while among girls 28 g [ 53 ]. The higher fish intake among males, even though many studies indicate that women often have healthier food choices than men [ 54 , 55 , 56 ], might be due to the fact that men simply consume bigger food portions [ 57 , 58 ] and more energy [ 59 ], but also more animal protein [ 60 ] than women.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in another study among Polish young adults aged 20–26, nine percent of them declared to consume fish and fish products several times a week, 31.5% once a week, 53.5% three times a month or less, and 6% declared not to consume fish at all. Interestingly, more men than women declared to consume them several times a week and once a week [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation could be more age variation in that study with a bias towards younger people. Other Polish studies showed that a number of hours spent in a sitting position, for both sexes, increases as age progresses [ 64 ]. Own results might suggest that males who were very active in leisure time needed a lot of time for rest and they could prefer passive resting in a sitting position, whilst in females sitting time could be a means of relaxation after strenuous work in the house and around the house.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that men and women tend to prefer divergent tastes and consume different types of food. Women usually show higher consumption of fruits and vegetables, increased dietary fiber intake, and lower fat intake, aligning with overall healthier food choices, thus demonstrating greater motivation for weight control ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%